‘You have nowhere to go (and i do)’. How fear of contagion affects migrant domestic workers - Bofill-Poch, Sílvia; Gregorio Gil, Carmen (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2021)
In the current COVID-19 context, we analyze how fear of contagion impacts on the working conditions of female migrant domestic workers in Spain. The article opens up the liminality in which the conditions of domestic work reproduction, and its regulatory framework, place these workers. It focuses on three related dimensions. First, how the power relations between workers, the person who is cared for and the family are reworked, and the new forms of coexistence within the households that it entails. Second, the emotional overload that home lockdown and social isolation means for these female workers. Third, how the gender, class and race boundaries between “us” and “others” are reshaped within the framework of domestic work servile relationships. Fear as a social category stems from a labour and immigration regulatory framework that deprives these female workers of their rights, and from a care economy that neglects and makes invisible the abuses and suffering that characterize this sector.
Keywords: domestic work; female migrants; COVID-19; fear; liminality